Fifty years of European ungulate dietary studies: a synthesis ... - Spitzer, Robert; Felton, Annika; Landman, Marietjie; Singh, Navinder; Widemo, Fredrik; Cromsigt, Joris (Dryad, 2020)
Over recent decades, ungulate populations across Europe have undergone a rapid recovery. While this constitutes a conservation success, there is increasing concern about their impacts on shared resources with humans. Understanding ungulate food choices is crucial for predicting such impacts. Numerous studies have focused on single species or communities at narrow spatial scales. Here, we used 265 published diets from 87 European studies to investigate patterns of resource use by four common deer species (moose Alces alces, red deer Cervus elaphus, roe deer Capreolus capreolus, and fallow deer Dama dama), and wild boar Sus scrofa at the continental scale. On average, deer diets separated mostly along a gradient from grass to browse. Fallow deer diets contained the most and moose diets the least amount of grass, but we also found large intraspecific variation among all deer species. Diets of roe deer, a presumed browser, frequently contained ≥ 25% grass. Wild boar diet contained grass in amounts similar to red ... : The dataset contains 265 diet profiles of five ungulate species (moose, roe deer, red deer, fallow deer, and wild boar) which were extracted from the European literature and standardized into 11 food categories and annual seasons. ...